Desempenho auditivo e qualidade de vida em crianças e adolescentes usuários de próteses auditivas - Pazini, Eduarda (2018)
This study aims to analyze the relationship between access to speech sounds and auditory behavior of the subject, quality of life, and auditory and situational variables. As a specific objective to characterize the audiological and situational profile of the participants. For this research, 305 medical records were analyzed and 26 subjects with ages ranging from 4 to 18 years, diagnosed with bilateral hearing loss, users of personal sound amplification products - PSAPs were assessed. As procedures were used: an initial interview; questionnaire on auditory behavior and quality of life - QL with parents /guardian and with children and adolescents; search for the minimum levels of response for the speech sounds by the test Six Ling (/a/, /i/, /u/, /ʃ/, /s/ e /m/). It was correlated the access to speech sounds with the auditory behavior of the child or adolescent and quality of life, as well as with the quality of life and the situational variables. Considering the results: there was a correlation between the speech access sounds (with PSAP) and the auditory behavior, how much better access the subject has to the analyzed sounds the better their auditory behavior. In the quality of life (QL) correlations of subjects- with Ling Sounds and PSAPs from the parent/guardian’s point of view, the physical capacity presented significant results with the use of PSAP in the vowel /a/ e in the fricative /ʃ/. It is possible to observe a positive correlation and statistical significance between the access to the sound of the vowels /a/ and /i/, including the nasal /m/ in the emotional aspect in the children and adolescents’ responses, allowing to infer that, the greater the access to the speech sounds by the child or adolescent, the better the self-perception of quality of life. It was concluded that the use of hearing aids was statistically significant so that children and adolescents with hearing impairment can more easily achieve speech sounds, aiding in auditory behavior and improvement in quality of life.